Arome Enterprise / Syarif Farhan Mohd Fauz...[et al.] - Mohd Fauzi, Syarif Farhan; Mohd Zaini, Muhammad Jaffrey Daniel; Mat Zabidi, Muhammad Danial Fitri; Baharim, Muhammad Syahir; Muhd Awaludin, Nazifa Nurinhuda (2019)
Arome Enterprise's mission is to be the most one international desire fragrance. The company's plan to achieve the mission by using an online medium and direct mailing. By using this method, people around Malaysia can easily purchase the perfume without having to go out from their house or even from their state. Nowadays, customers can shop everything they want at just one click. Due to that technology, Arome Enterprise want to implement the same way as the current trends. Arome Enterprise targets are cars and all generations of man and woman as the arome is suitable for every age. For the beginning, the company will be targeting students and hardworking workers that are tend to have their classes or offices far from their home, and they have to stay focus all the time. Arome Enterprise can overcome this problem thus helping the company to gain profits from it. By having the customers, Arome Enterprise will be more well known in the future. In order to achieve company's mission, Aroma Enterprise have to face some risks when entering perfume markets as there are many competitors and problems will occur.